Law and psychoanalysis: close intertwining between Hans Kelsen and Sigmund Freud (Revista Justiça do Direito, 2021)
This paper offers an original analysis of the interconnections between law and psychoanalysis through the personal and academic exchanges between Hans Kelsen (1881-1973) and Sigmund Freud (1856-1939). After a brief analysis of the similar cultural background of both scholars as Jews who grew up in fin-de-siècle Vienna, the text focuses on the personal encounters between them and subsequently analyzes Kelsen's reception of Freud's work in “The State-Concept and Social-Psychology” (Der Begriff des Staates und die Sozialpsychologie). Kelsen’s text was originally published in 1922 in Freud’s review, Imago, resulting from a conference he held at the Viennese Psychoanalytical Society. This paper analyzes the relevance of Freud’s theory to the construction of the Pure Theory of Law, especially regarding his concept of the state. Furthermore, it presents a new hypothesis for the subjective reasons behind Kelsen’s attraction to psychoanalysis, and for his admiration of Freud, which it tries to understand through the personal context of Kelsen’s life. Finally, it deals with the possible influence of Kelsen on Freud's work, especially with regards to the term "Super-Ego."